Percutaneous atrial septal defect closure using transesophageal echocardiography without fluoroscopy in a pregnant woman: a case report (Medical Journal of Indonesia, 2020)
Transcatheter closure is the treatment of choice for atrial septal defect (ASD); it has good efficacy and minimal complications. However, this approach in a pregnant woman is limited due to the risk of radiation exposure. A novel fluoroscopy-free technique has been introduced to reduce x-ray exposure. This case reported the experience of an ASD transcatheter closure in a pregnant woman without fluoroscopy guidance. To the best of our knowledge, this is the first successful fluoroscopy-free technique for transcatheter closure in Indonesia. The case is a 26-year-old primigravida at 26 weeks gestational age with secundum ASD and pulmonary hypertension. Transcatheter closure was successfully performed with a Cera ASD occluder (Lifetech Scientific Corporation, China) no. 28 mm guided by transesophageal echocardiography. During the procedure, transient supraventricular tachycardia was developed. There were no other major or minor periprocedural complications. ASD transcatheter closure in a pregnant woman without fluoroscopy is feasible, safe, and effective.